Cost of inpatient heart failure care and 30-day readmissions in the United States. (15th April 2021) - Kwok, Chun Shing; Abramov, Dmitry; Parwani, Purvi; Ghosh, Raktim K.; Kittleson, Michelle; Ahmad, Fozia Z.; Al Ayoubi, Fakhr; Van Spall, Harriette G.C.; Mamas, Mamas A.
Abstract: Background: Heart failure hospitalizations are a major financial cost to healthcare systems. This study aimed to evaluate the costs associated with inpatient hospitalization. Methods: Patients with a primary diagnosis of heart failure during a hospital admission between 2010 and 2014 in the U.S. Nationwide Readmission Database were included. The primary outcome was total cost defined by direct cost of index admission and first readmission within 30-days. Results: A total of 2, 645, 336 patients with primary heart failure were included in the analysis. The mean ± SD total cost overall was 13, 807 ± 24, 145; with mean total costs of 15, 618 ± 25, 264 for patients with 30-day readmission and 11, 845 ± 22, 710 for patients without a readmission. The comorbidities strongly associated with increased cost were pulmonary circulatory disorder (OR 26.24 95% CI 20.06–34.33), valvular heart disease (OR 25.42 95% CI 20.65–31.28) and bleeding (OR 5.96 95% CI 5.47–6.50). Among hospitalized patients, 12.6% underwent an invasive diagnostic procedure or treatment. The mean cost for patients without invasive care was 10, 995. This increased by 129, 547, 119, 769, 251, 110 and 293, 575 for receipt of circulatory support, intra-aortic balloon pump, LV assist device and heart transplant. The greatest mean additional cost annually was associated with receipt of coronary angiogram (26, 282 per person for a total of (728.5 million) and mechanical ventilation (54, 529 per person for a total of 501.7 million). Conclusion: In conclusion, the costs associated with inpatient heart failure care are significant, and the major contributors to inpatient costs are comorbidities, invasive procedures and readmissions. Highlights: Costs associated with heart failure hospitalizations in the United States vary greatly among hospitalized patients Biggest comorbidity contributors to increased inpatient costs are pulmonary disorders, valvular heart disease, and bleeding Invasive procedures are common in patients hospitalized with heart failure and significantly increase hospitalization costs Heart Failure readmissions are frequent, and readmissions also significantly contribute to total hospitalization costs